Good strategy, bad strategy : the difference and why it matters - Rumelt, Richard P. (New York : Crown Business, 2011)
Developing and implementing a strategy is the central task of a leader, whether the CEO at a Fortune 100 company, an entrepreneur, or a government official. Richard Rumelt shows that there has been a growing and unfortunate tendency to equate Mom-and-apple-pie values, fluffy packages of buzzwords, motivational slogans, and financial goals with 'strategy.' He debunks these elements of 'bad strategy' and awakens an understanding of the power of a 'good strategy.' He defines a good strategy as a specific and coherent response to- and an approach for overcoming- the obstacles to progress. A good strategy works by harnessing and applying power where it will have the greatest effect in respect to the challenge. Thus, Rumelt argues that the heart of a good strategy is insight into the true nature of the situation, so that the hidden power in a situation can be discerned and an appropriate response be devised. He shows you how insight can be cultivated using a wide variety of tools for guiding your own thinking and to that end he presents nine sources of power- ranging from leverage to effectively focusing on growth- that are eye-opening yet pragmatic tools that can be immediately put to work. -- from Publisher Description
Argues that a manager's central responsibility is to create and implement strategies, challenges popular motivational practices, and shares anecdotes discussing how to enable action-oriented plans for real-world results.
Good strategy is unexpected -- Discovering power -- Bad strategy -- Why so much bad strategy? -- The kernel of good strategy -- Using leverage -- Proximate objectives -- Chain-link systems -- Using design -- Focus -- Growth -- Using advantage -- Using dynamics -- Inertia and entropy -- Putting it together -- The science of strategy -- Using your head -- Keeping your head.
Includes bibliographical references and index.
Keywords: Strategic planning; Strategy; Planning; Strategic planning; Strategy; Planning